HIGHLY FILLED COMPOSITES IN POLYMER PACKAGING TECHNOLOGIES - ІСКАНДАРОВ, Р. Ш.; СЛЄПЦОВ, О. О.; ПУШКАРЕВ, Д. В.; ОСАУЛЕНКО, С. І. (Technologies and Engineering, 2022)
Purpose. Creation of highly filled polymer composites suitable for use in polymer packaging technologies. Methodology. The main physical and mechanical properties of the test samples were determined – strength and relative elongation at break according to ISO 527-2:2012, density according to ISO 1183-1:2019. Determination of the melt flow index of composites was carried out according to ISO 1133:1997 on a capillary viscometer of constant pressure at a temperature of (190±0.5)°C and a load weight of 2.16 kg. The effect of shape memory was evaluated by the non-creasing coefficient value determined by the method of oriented creasing. Findings. Introduction of a filler based on mineral calcium carbonate into low-density polyethylene in an amount of more than 30% by weight. leads to obtaining a polymer composite with a "paper-like effect". This material is promising for use in the packaging industry for the production of multilayer packaging for dairy products. The introduction of a significant amount of filler allows to reduce the use of petroleum raw materials, which is economically and environmentally beneficial. Preliminary drying of the applied filler ensures a satisfactory level of physical and mechanical properties of the composite. Introduction of up to 5% by mass. compatibilizer – a grafted copolymer of polyethylene and maleic anhydride provides interaction between the filler and the polymer matrix, which positively affects the mechanical properties of the composite. Originality. The dependence of the physical and mechanical properties of the highly filled polymer composite based on polyethylene on the content of the filler, its initial humidity and the presence of a compatibilizer in the system was established. Practical value. The composition of a highly filled polymer composite based on polyethylene, which has a "paper-like effect" and has satisfactory physical and mechanical properties, has been established and can be used for the manufacture of packaging.